Quantitative Assessment of Perfusion and Vascular Compromise in Perforator Flaps using a Near-Infrared Fluorescence Guided Imaging System - Matsui, Aya (2009)
BACKGROUND: Techniques currently used to determine flap perfusion are mainly subjective, with the majority of reconstructive surgeons still relying on clinical examination. In this study, we demonstrate the use of near-infrared (NIR) fluorescence angiography to directly quantify normal and abnormal perfusion in perforator flaps. METHODS: Indocyanine green was intravenously injected into anesthetized adult pigs (n = 38). A custom NIR fluorescence imaging system was employed for image acquisition and quantitation. Thirty-nine flaps were designed based on identified perforators, and post-operative imaging was performed for comparison. In select flaps, isolated occlusion of the arterial and venous pedicle was performed. In select flaps, vascular spasm was induced by local irrigation of the vessels with epinephrine. The fluorescence intensities (FI) of select regions-of-interest (ROI) were quantified. From these data, we defined two indices for abnormal perfusion: the T(max) ratio (TR) and the drainage ratio (DR). RESULTS: We identified a normal pattern of perfusion prior to flap elevation, composed of a distinct FI peak at maximal arterial inflow followed by a smooth drop representing venous drainage. Delay of this peak after flap elevation, as indicated by TR, identified vascular spasm and arterial occlusion (p < 0.0001). Abnormal fall of FI after this peak, as indicated by DR, identified venous occlusion (p < 0.0001). CONCLUSIONS: Quantitation of FI by NIR angiography accurately characterizes arterial and venous compromise. Our technique can assess perfusion characteristics during the intra-operative and post-operative periods, and therefore complements clinically-based subjective criteria now used for flap assessment.